SMEDDS of Citrus hystrix ethanolic extract improves cardiac and hepar histopathology profile on doxorubicin-induced rats - Dhania Novitasari; Prisnu Tirtanirmala; Nindi Wulandari; Layung Sekar Sih Wikanthi; Ade Safitri; Ediati Sasmito (Indonesian Journal of Cancer Chemoprevention, 2015)
Citrus hystrix D.C. (kaffir lime) peel contains several flavonoids including rutin, naringenin, hesperidin. C. hystrix peel ethanolic extract (ChEE) has shown its potency as cardioprotector agent in chemotherapy. However, there  are  limitations  to  the  utilization  of  ChEE due to its  poor  water  solubility  and  low  oral bioavailability.  Accordingly,  self-microemulsifying drug delivery system (SMEDDS) formulations were developed to improve the oral absorption of flavonoids. Tween 80, Corn oil, and propylene glicol (5:1:1ml) were combined to form ChEE-SMEDDS. The present study is to evaluated ChEE-SMEDDS for their physicochemical  properties and in vivo using combination with doxorubicin to see blood serum alanine aminotransferase (ALT), aspartate aminotransferase (AST), nitrit oxide (NO) activity and also cardio-hepato-histopathology of female Sprague Dawley rats. The results showed that ChEE-SMEDDS repaired cardio-hepato-histopathology profile of doxorubicin -induced rats, but did not reduce serum activity of NO, ALT and AST. These  results indicated that ChEE-SMEDDS has potency to be developed and improved as cardio-hepato-protector agent in chemotherapy.Keywords: Citrus hystrix D.C., SMEDDS, Cardio-hepatoprotector, Histopathology, Chemoterapy